(untitled) (Journal of Oriental Studies, 2025)
This article discusses a relatively rare scientific field in Kazakh Turkology—research on the Ottoman-Turkish language. In contemporary Turkish lexicography, the Ottoman language is referred to as Osmanlıca or Osmanlı Türkçesi, as seen in sources like Kamus-i Türki and The Explanatory Dictionary of the Turkish Language. In Soviet and Russian Turkology, the term Osman-Turkish language (османско-турецкий язык) was established, which can be translated into Kazakh as осман-түрік тілі. The purpose of this study is to review the representation and scholarly interpretation of this language in Kazakh Turkological research, as well as to provide insight into the thematic and content-specific features of Kazakh-language materials on this subject. In our research, we have utilized historical and lexical studies, providing illustrative examples to highlight the relevance of this topic. Alongside foreign studies, we have referenced works translated from Turkish into Kazakh. Additionally, we examined the phenomenon of so-called "Sovietisms" in academic publications from both the Soviet period and modern times, discussing their reflection in Kazakh-language content. To provide an overview of textbooks on the Ottoman-Turkish language, we referred to E. A. Grunina’s Guide to the Ottoman-Turkish Language (Руководство по османо-турецкому языку) and the Turkish scholar Hayati Develi’s Osmanlı Türkçesi Grameri-I (Ottoman Language Grammar). We outlined the thematic content of these works and analyzed the sources they rely on, also including information on their modern digital availability. As highlighted in the article, even within Turkish scholarship, the term Osman-Turkish language is not uniformly assessed. Some studies argue that it was not a literary language but rather a dialect or vernacular spoken by the populace. We also referenced works that analyze the teaching of Ottoman-Turkish within the context of folk pedagogy during the Seljuk and early Ottoman periods, incorporating explanations of specific terms and concepts in Kazakh. Furthermore, we addressed discussions in Kazakh-language content regarding the "Ankara dialect," comparing it with research on the "Istanbul dialect" and its role in shaping modern standard Turkish. We emphasized the historical significance of Istanbul in this linguistic evolution. Drawing on studies by Turkish scholars, we explored the works of Mehmet Akif Ersoy, one of the key poet-transmitters between the Ottoman-Turkish language and modern Turkish. Additionally, we provided information on a scholarly cataloging project involving Ottoman-Turkish manuscripts preserved at the National Library of Kazakhstan. Keywords. Ottoman Empire, Ottoman-Turkish language, Young Turks, Cyprus, Sovietism, normative lexicon, cataloging.